2019
DOI: 10.1021/acs.chemrestox.9b00047
|View full text |Cite
|
Sign up to set email alerts
|

Sucralose-Enhanced Degradation of Electronic Cigarette Liquids during Vaping

Abstract: Electronic cigarette liquids (e-liquids) with sweetener additives such as sucralose, a synthetic chlorinated disaccharide, are popular among some e-cigarette consumers; sucralose can be added either by the manufacturer or by the consumer. The prevalence of sucralose in commercial e-liquids is not known, nor is the typical concentration of sucralose when present; labels are not required to disclose ingredient information. Here, we report the effects of sucralose on e-liquid degradation upon e-cigarette vaping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…A fully charged JUUL device was equipped with a JUUL ‘Classic Menthol’ 5% nicotine pod and vaped using the CORESTA puff method (55 mL puff volume, 3 s long) and employed vaping methods described previously 16 17. The JUUL device (+e-liquid pod) was weighed before and after the generation of five puffs to obtain the mass of aerosol produced over the five puffs.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…A fully charged JUUL device was equipped with a JUUL ‘Classic Menthol’ 5% nicotine pod and vaped using the CORESTA puff method (55 mL puff volume, 3 s long) and employed vaping methods described previously 16 17. The JUUL device (+e-liquid pod) was weighed before and after the generation of five puffs to obtain the mass of aerosol produced over the five puffs.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…Generally, production of aldehydes such as formaldehyde, acetaldehyde, and acrolein also increases when emissions are generated using higher inhalation conditions. Regarding this observation, the results presented when a low vaping regimen is used to characterize a third-generation atomizer [39,40,41,42] would probably be significantly different with the use of an intense vaping regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Vreeke et al [35] observed that e-liquid containing 10% flavoring compound was associated with increased carbonyls in aerosol compared with e-liquids containing only VG:PG. Duell et al [39] observed that the concentrations of aldehydes (propionaldehyde, acetaldehyde, glycolaldehyde, and acrolein) increased as sucralose concentration in the e-liquid increased. The relative concentrations of carbonyls in the aerosol have varied from study to study [36,38].…”
Section: Plos Onementioning
confidence: 99%
“…Additionally, Vreeke et al [35] reported that the addition of triacetin, a common flavor additive, increased levels of formaldehyde hemiacetals. Duell et al [39] observed that formaldehyde hemiacetals increased with increasing concentrations of sucralose added to the e-liquid. Erythropel et al [68] reported carryover rates for both aldehydes and corresponding acetals to be 50-80% of the original concentration in e-liquid.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation